Methionine-to-Cysteine Recycling in Klebsiella aerogenes - Seiflein, Thomas A. (American Society for Microbiology, 2001)
In the enteric bacteria Escherichia coli and Salmonella enterica, sulfate is reduced to sulfide and assimilated into the amino acid cysteine; in turn, cysteine provides the sulfur atom for other sulfur-bearing molecules in the cell, including methionine. These organisms cannot use methionine as a sole source of sulfur. Here we report that this constraint is not shared by many other enteric bacteria, which can use either cysteine or methionine as the sole source of sulfur. The enteric bacterium Klebsiella aerogenes appears to use at least two pathways to allow the reduced sulfur of methionine to be recycled into cysteine. In addition, the ability to recycle methionine on solid media, where cys mutants cannot use methionine as a sulfur source, appears to be different from that in liquid media, where they can. One pathway likely uses a cystathionine intermediate to convert homocysteine to cysteine and is induced under conditions of sulfur starvation, which is likely sensed by low levels of the sulfate reduction intermediate adenosine-5′-phosphosulfate. The CysB regulatory proteins appear to control activation of this pathway. A second pathway may use a methanesulfonate intermediate to convert methionine-derived methanethiol to sulfite. While the transsulfurylation pathway may be directed to recovery of methionine, the methanethiol pathway likely represents a general salvage mechanism for recovery of alkane sulfide and alkane sulfonates. Therefore, the relatively distinct biosyntheses of cysteine and methionine in E. coli and Salmonella appear to be more intertwined in Klebsiella.